Medical Technologies: Pharmaceutical Cosmetology, Cosmeceuticals – Opportunities and Limitations - Shapovalova, Viktoriia; Osyntseva, Alina; Shapovalov, Valentyn (Annals of Mechnikov's Institute, 2026)
Introduction. Pharmaceutical cosmetology is an interdisciplinary field at the junction of pharmacy, dermatology, and aesthetic medicine. The active development of cosmeceuticals is associated with the growing demand for products that combine a cosmetic effect with a biological effect on the skin. At the same time, the lack of a single regulatory status and mandatory randomized clinical trials creates several scientific and legal challenges. Purpose. To analyze the possibilities and limitations of cosmeceuticals in pharmaceutical cosmetology from the standpoint of modern medical technologies, evidence-based medicine, and pharmaceutical care. Methods. A systematic literature review was conducted using the PRISMA protocol using the PubMed, Scopus, Web of Science and Cochrane Library databases for 2015–2026. Out of 1243 publications, 62 sources with evidence levels I–II according to the Oxford Centre for Evidence-Based Medicine were selected after screening. Results. The article summarizes modern technological platforms of cosmeceuticals, including nanoemulsions, liposomes, multiple emulsions, and probiotic complexes, which increase the bioavailability of active ingredients by 3-5 times. The main groups of cosmeceutical active ingredients and their clinical efficacy in photoaging, acne, hyperpigmentation and alopecia are systematized. The importance of pharmaceutical care and consulting algorithms for increasing the safety of cosmeceutical use is shown. The prospects for personalized cosmeceuticals based on genetic tests and artificial intelligence are identified. Regulatory gaps in the USA, EU and Ukraine are outlined. Conclusions. Cosmeceuticals are a promising direction of integration of pharmacy, dermatology, and digital technologies, which demonstrates proven effectiveness in mild forms of dermatoses and prevention of photoaging. Further development requires standardization of the term, development of national regulatory approaches and implementation of pharmacovigilance systems.